2023
DOI: 10.1039/d2fo03016k
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic acid-enriched phospholipids alleviate glucose and lipid metabolism in spontaneously hypertensive rats with CD36 mutation: a precise nutrition strategy

Abstract: Previous studies found that Eicosapentaenoic acid-enriched phospholipid (EPA-PL) alleviated glucose and lipid metabolism that accompanied an increase of cluster of differentiation 36 (CD36). However, the effects of EPA-PL on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…121,123 And EPA-enriched phospholipids have been proved to alleviate hypertension in spontaneously hypertensive rats with CD36 mutation. 124 In terms of brain health, n-3 PUFA plays an important role in prevention and treatment of behavior, mood, and other brain disorders, especially phospholipids form for the effective cross of blood−brain barrier (BBB). 49,125,126 are also proved effective on alleviating neurological disorders.…”
Section: Amelioration Of Tmao-related Possible Health Risks By Seafoo...mentioning
confidence: 99%
See 1 more Smart Citation
“…121,123 And EPA-enriched phospholipids have been proved to alleviate hypertension in spontaneously hypertensive rats with CD36 mutation. 124 In terms of brain health, n-3 PUFA plays an important role in prevention and treatment of behavior, mood, and other brain disorders, especially phospholipids form for the effective cross of blood−brain barrier (BBB). 49,125,126 are also proved effective on alleviating neurological disorders.…”
Section: Amelioration Of Tmao-related Possible Health Risks By Seafoo...mentioning
confidence: 99%
“…Furthermore, researches showed that EPA in phospholipids form, especially in phosphoethanolamine plasmalogens, form exerts superior antiatherosclerosis effects to triglyceride form . Besides, astaxanthin, taurine, sea cucumber cerebrosides, and sea cucumber sterol sulfate are also confirmed to be effective. , And EPA-enriched phospholipids have been proved to alleviate hypertension in spontaneously hypertensive rats with CD36 mutation . In terms of brain health, n-3 PUFA plays an important role in prevention and treatment of behavior, mood, and other brain disorders, especially phospholipids form for the effective cross of blood–brain barrier (BBB). ,, Mussel oligopeptides and fucoxanthin are also proved effective on alleviating neurological disorders .…”
Section: Amelioration Of Tmao-related Possible Health Risks By Seafoo...mentioning
confidence: 99%